RESPON PERTUMBUHAN, PRODUKSI DAN KANDUNGAN SENG (Zn) TANAMAN PADI (Oryza sativa L.) TERHADAP TEKNIK PEMBERIAN DAN DOSIS PUPUK ZINK SULFAT - Sunar Sunar; Tira Rinda Gustina; Nikmah Nikmah (Fakultas Pertanian Universitas Borobudur, 2021)
Zinc (Zn) is an essential micro element that is needed by plants and also inhumans. The importance of the adequacy of Zn minerals in food is not yet fullyunderstood by the public. Rice as a staple food has the potential to provide microelements Zn, but the content of micro nutrients Zn in rice is still low than therecommended requirement. This study aims to determine the response of growth,production and Zn content in rice to the technique of application (spray andspread) and dose of Zn Sulfate Heptahydrate (ZnSO4) fertilizer applied to riceplants (Oryza sativa L.) which was carried out in the field. The study wasarranged in a randomized block series (RAK) with eight treatments consisting ofT1D0 (Spread Technique × Dose 0 kg), T1D1 (Spread Technique × Dose 8 kg),T1D2 (Spread Technique × Dose 12 kg) T1D3 (Spread Technique × Dose 16 kg),T2D0 (Spray Technique × 0 kg Dosage), T2D0 (Spray Technique × 8 kg Dose),T2D2 (Spray Technique × 12 kg Dose), T2D0 (Spray Technique × 16 kg Dose).The results showed that spraying zinc sulfate heptahydrate (ZnSO4) 12kg/haincreased rice production by 20% and spraying zinc sulfate heptahydrate(ZnSO4) 16 kg/ha increased zinc content in rice by 5.3%.Keywords: Rice, Zinc, Zinc Sulphate Heptahydrate Fertilizer